2023
DOI: 10.1021/jacs.3c08331
|View full text |Cite
|
Sign up to set email alerts
|

Iridium Acylnitrenoid-Initiated Biomimetic Cascade Cyclizations: Stereodefined Access to Polycyclic δ-Lactams

Eleonora Tufano,
Euijae Lee,
Matteo Barilli
et al.

Abstract: Ring-fused azacyclic compounds are important building units in the synthesis of biorelevant natural products, pharmaceutical agents, and molecular materials. Herein, we present a new approach to these condensed azacycles by a biomimetic cascade cyclization of arylalkenyl dioxazolones. This cascade reaction was found to proceed with excellent stereoselectivity and a high functional group tolerance. The substrate scope of arylalkenyl dioxazolones turned out to be highly flexible and extendable to additional ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 110 publications
0
2
0
Order By: Relevance
“…Transition-metal-catalyzed cross-coupling reactions have emerged as a pivotal technique for the construction of carbon–carbon and carbon–heteroatom bonds, which play an instrumental role in synthesizing valuable organic molecules . Among these, reductive cross-couplings of two electrophiles offer a distinct advantage over conventional methods by circumventing the use of moisture- and air-sensitive organometallic reagents. , Asymmetric reductive cross-coupling between diverse unsaturated bonds, such as a CO bond with a CN bond or different CO bonds, provides a rapid avenue to generate synthetically and biologically relevant β-amino alcohols and 1,2-diols with adjacent stereocenters (Figure A). While several advancements have been achieved in the realm of such transformations catalyzed by transition metals like copper, chromium, and scandium, this methodology still encounters inherent challenges .…”
Section: Introductionmentioning
confidence: 99%
“…Transition-metal-catalyzed cross-coupling reactions have emerged as a pivotal technique for the construction of carbon–carbon and carbon–heteroatom bonds, which play an instrumental role in synthesizing valuable organic molecules . Among these, reductive cross-couplings of two electrophiles offer a distinct advantage over conventional methods by circumventing the use of moisture- and air-sensitive organometallic reagents. , Asymmetric reductive cross-coupling between diverse unsaturated bonds, such as a CO bond with a CN bond or different CO bonds, provides a rapid avenue to generate synthetically and biologically relevant β-amino alcohols and 1,2-diols with adjacent stereocenters (Figure A). While several advancements have been achieved in the realm of such transformations catalyzed by transition metals like copper, chromium, and scandium, this methodology still encounters inherent challenges .…”
Section: Introductionmentioning
confidence: 99%
“…Hydroxyquinolines are commercially available and offer a wide range of substitutions. We have previously reported that oxyquinolinates are excellent bidentate ligands to modulate the photocatalytic activity of Pt complexes. , Additionally, [IrCp*Cl­(N^O)] complexes have been employed as organometallic catalysts in chemoselective transformations, where the selectivity was controlled by the ligand nature. However, these complexes have not been employed as photocatalysts or in transfer hydrogenation reactions. In this context, we aimed to synthesize iridium complexes with Cp* and 8-oxyquinolinate ligands capable of catalyzing both carbonyl reduction (TH reactions) and photomediated processes like halogen reduction and alkene isomerization (right, Figure b).…”
Section: Introductionmentioning
confidence: 99%